Airborne geophysical characterization of geotectonic relationships in the southern Ribeira Belt, Luís Alves Craton, and northern Dom Feliciano Belt, Brazilian Shield. Issue 4 (11th March 2016) - Hartmann, Léo Afraneo; Savian, Jairo Francisco; Lopes, William Ribeiro
ABSTRACT: In many Precambrian provinces, the understanding about the tectonic history is restrained by the limited exposure of rocks so that aerogeophysical data can provide information below the surface cover of sediments, soil, and water to build a tectonic model of the region. However, the tectonic evolution of cratons and shear zones is very complex due to scarce aerogeophysical and geological data. The integrated observation of geology, aerogammaspectrometry, and aeromagnetometry of the Brazilian Shield, states of Santa Catarina, Paraná, and southern São Paulo, is enhanced by a 2011 high-resolution aerogeophysical survey. The Ponta Grossa and Florianópolis dike swarms show two sets of linear high magnetic signal. Peralkaline–carbonatitic complexes are observed in all images, e.g. Jacupiranga, Tunas, and Anitápolis. Three main geotectonic provinces are apparent in the shield. The Dom Feliciano Belt has two domains in terms of radioelements K, Th, and U. This belt includes granitic rocks of the Florianópolis Batholith, Brusque Group schists, and Itajaí Basin of sedimentary and volcanic rocks. The Luís Alves Craton has mostly the Santa Catarina Granulitic Complex and other gneisses. The craton has patches of high emission rates and extends to the northeastern extreme of the studied area with a high-contrast magnetic signal in most of the unit. The Ribeira Belt also has high in gammaspectrometric images, although less homogeneous than the Dom Feliciano Belt. This belt contains granitic complexes, gneisses, and schists and has a low magnetic signal with patches of high analytical signal amplitude. Shear zones delimit different geotectonic units, but are also significant in the Ribeira Belt. The Luís Alves Craton is the most complex unit, as seen in ternary K + eTh + eU images, requiring the future discrimination of small features. This novel study of the Brazilian Shield based on new geophysical data supports the classification of the proposed main geotectonic units.